2007
DOI: 10.1523/jneurosci.4229-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Catechol-O-Methyltransferase and Dopamine D4 Receptor Genotypes on Neurophysiological Markers of Performance Monitoring

Abstract: Dynamic adaptations of one's behavior by means of performance monitoring are a central function of the human executive system, that underlies considerable interindividual variation. Converging evidence from electrophysiological and neuroimaging studies in both animals and humans hints at the importance of the dopaminergic system for the regulation of performance monitoring. Here, we studied the impact of two polymorphisms affecting dopaminergic functioning in the prefrontal cortex [catechol-O-methyltransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
111
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 50 publications
(76 reference statements)
17
111
0
Order By: Relevance
“…This conclusion is supported by recent functional MRI and electrophysiological evidence linking the brain's error response to genetic markers of dopamine function ( Frank et al 2007;Klein et al 2007;Krämer et al 2007). Additionally, patients with Parkinson's disease show reduced ACC responses to errors that are partly moderated by dopaminergic medication (Frank et al 2004).…”
Section: Discussionmentioning
confidence: 65%
“…This conclusion is supported by recent functional MRI and electrophysiological evidence linking the brain's error response to genetic markers of dopamine function ( Frank et al 2007;Klein et al 2007;Krämer et al 2007). Additionally, patients with Parkinson's disease show reduced ACC responses to errors that are partly moderated by dopaminergic medication (Frank et al 2004).…”
Section: Discussionmentioning
confidence: 65%
“…In Val allele carriers increased ERN (Osinsky et al, 2012) or a trend to an increased ERN (Kramer et al, 2007), no effect on the ERN but increased Pe in Met homozygotes .…”
Section: Comt Val 158 Met (Rs4680)mentioning
confidence: 85%
“…The DRD4 -521C allele has been associated with schizophrenia (Okuyama et al, 1999;Xing et al, 2003;Allen et al, 2008) and healthy individuals homozygous for the C allele showed a decreased ERN and decreased post-error slowing compared to T homozygotes (Kramer et al, 2007).…”
Section: Drd4 C-521tmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of genetic factors on error processing and response monitoring functions has frequently been studied in the past (Klein et al, 2007;Krämer et al, 2007;Beste et al, 2010a). Until now, no study examined the role of neurotrophins for these im- portant cognitive functions.…”
Section: Discussionmentioning
confidence: 99%